Surgical Remodeling of the Left Ventricle in Patients with Post-Infarction Dilation and Heart Failure - P. V. Chernyavsky; M. Kh. Mazanov; I. A. Argir; N. M. Bikbova; S. Yu. Kambarov; M. A. Sagirov; A. V. Dublev; A. V. Timerbaev; N. I. Kharitonova (Неотложная медицинская помощь, 2022)
INTRODUCTION The cause of heart failure in patients with coronary artery disease after anterior myocardial infarction may be dilatation of the cavity of the left ventricle (LV) with subsequent unfavorable course of the disease. In the case of early reperfusion, which prevents transmural myocardial necrosis, the damaged segment more often becomes akinetic than dyskinetic. Surgical remodeling of the left ventricle (SRLV) is aimed at reducing the volume and restoring its elliptical shape by eliminating scars in the akinetic and/or dyskinetic segments.AIM OF STUDY To evaluate the survival of patients with chronic heart failure (CHF) who had anterior wall myocardial infarction in the early and late periods after surgical remodeling of the left ventricle, in combination with coronary bypass grafting and/or interventions on the mitral valve.MATERIAL AND METHODS The study included 99 patients with coronary artery disease (CAD) who had myocardial infarction of the anterior LV wall and with severe heart failure, who underwent surgical LV remodeling in the period from 2002 to 2020. The analysis of early and long-term results was carried out. The risk factors influencing lethality were determined.The mean age of the patients was 56.0±10.2 years (from 23 to 81 years). The vast majority of patients (90%) were men. LV ventriculoplasty was combined with coronary bypass grafting in 97 (98%) patients, with mitral valve repair in 2 (2%) patients, with mitral valve replacement in 2 (2%) patients.RESULTS In the early postoperative period, all patients showed an improvement in global LV systolic function. The ejection fraction (EF) of the left ventricle increased from the average preoperative average value of 34.2±3.7% to 43±4.2% in the postoperative period (р<0,001). Left ventricular end systolic volume index (LVESV) decreased from 71.4±15.3 ml/m2 to 43.8±9.6 ml/m2, respectively (р<0,001). In the early postoperative period, 5 (5%) patients used the following means of mechanical hemodynamic support: intra-aortic balloon pump (IABP), non-implantable device for temporary support of the left ventricle (LVAD) and extracorporeal membrane oxygenation (ECMO). The 30-day mortality rate after LVESV was 6%. Prior to surgery, all patients had NYHA functional class (FC) III or IV. In the postoperative period, all patients experienced regression of heart failure symptoms and improved exercise tolerance. NYHA functional class improved to I and II in 100% of cases. Using univariate analysis, it was possible to determine that EF ≤30%, LVESV ≥80 ml/m2 and pulmonary artery pressure (PAP) >60 mm Hg. were risk factors for hospital mortality. The overall fifteen-year survival rate was 59.8±0.13%. The absence of readmission to the hospital due to recurrent angina pectoris, mitral valve dysfunction and progression of heart failure (HF) was 72% among surviving patients.CONCLUSION Surgical remodeling reduces the volume of the dilated left ventricle and restores its elliptical shape in patients with CAD after anterior myocardial infarction. The results of our study demonstrate an improvement in LV systolic function in all patients in the early postoperative period and low mortality, an acceptable fifteen-year survival rate, and a low readmission rate due to the progression of chronic heart failure (CHF).